Surgical management of complete penile duplication accompanied by multiple anomalies - Karaca, Irfan; TURK, Erdal; Ucan, A. Basak; Yayla, Derya; Itirli, Gulcin; Ercal, Derya (Canadian Urological Association Journal, 2014)
Diphallus (penile duplication) is very rare and seen once every 5.5 million births. It can be isolated, but is usually accompanied by other congenital anomalies. Previous studies have reported many concurrent anomalies, such as bladder extrophy, cloacal extrophy, duplicated bladder, scrotal abnormalities, hypospadias, separated symphysis pubis, intestinal anomalies and imperforate anus; no penile duplication case accompanied by omphalocele has been reported. We present the surgical management of a patient with multiple anomalies, including complete penile duplication, hypogastric omphalocele and extrophic rectal duplication.